2017
DOI: 10.15537/smj.2017.2.15077
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive and liberal fluid administration in major abdominal surgery

Abstract: Objectives:To determine whether perioperative fluid restrictive administration can reduce specific postoperative complications in adults undergoing major abdominal surgery.Methods:We searched the MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials, Google scholar, and article reference lists (up to December 2015) for studies that assessed fluid therapy and morbidity or mortality in patients undergoing major abdominal surgeries. The quality of the trials was assessed using the Jadad scoring syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…Interestingly, a recent large randomised controlled trial (RCT) assigning 2983 patients to either zero-balance or liberal strategy showed comparable disability-free survival outcome, although the zero-balance approach was associated with a higher rate of acute kidney injury [ 16 ]. As a matter of fact, this single study enrolled more patients than several previous RCTs regarding this topic, insofar, partially challenging previous results [ 18 20 ].…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, a recent large randomised controlled trial (RCT) assigning 2983 patients to either zero-balance or liberal strategy showed comparable disability-free survival outcome, although the zero-balance approach was associated with a higher rate of acute kidney injury [ 16 ]. As a matter of fact, this single study enrolled more patients than several previous RCTs regarding this topic, insofar, partially challenging previous results [ 18 20 ].…”
Section: Introductionmentioning
confidence: 89%
“…Literatürde hipotansiyon ve inotropik ilaçlardan kaçınılarak >2 mL kg sa -1 idrar çıkışının HİPEK sonrası böbrek hasarını önlemede yeterli olduğu belirtilmiştir (26) . Bir çalışmada, restriktif sıvı tedavisinin özellikle korkulan akut böbrek hasarı açısından etkili olmadığı, çok/az/çok az sıvı tedavileri ile artan şekilde daha çok intestinal perfüzyonun olumsuz etkilendiği bildirilmiştir (27) . Çalışmamızda, ameliyat boyunca liberal grupta ortalama 2.1 mL kg -1 sa -1 , restriktif grupta 1.1 mL kg -1 sa -1 idrar çıkışı olmuştur ve postoperatif ilk 7 gün takip edilen kreatinin değerleri normal sınırlarda seyretmiştir.…”
Section: Discussionunclassified
“…This inconsistency might be due to the prescription method of the treatment fluid and the surgical method applied to patients in the two stud-ies (11). Neutral findings in renal complications after abdominal surgeries between patients receiving liberal and restrictive regimens have been reported in meta-analysis and clinical trials, as well (10,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The level of tissue oxygenation is directly affected by the cardiac output and the volume of circulating fluid, keeping in mind that the excessive increase of fluid in circulation will apply extra cardiac loads (7,8). In general, the strategy of substituting the restrictive volume of fluids is acceptable for certain surgeries (9,10). Monitoring the renal function while maintaining the cardiac output will help find the optimum strategy of intraoperative fluid therapy.…”
Section: Introductionmentioning
confidence: 99%